2018
DOI: 10.1002/pola.29092
|View full text |Cite
|
Sign up to set email alerts
|

Amino‐functionalized hollow microporous organic nanospheres for pd supported catalysis and I2 uptake

Abstract: Amino‐functionalized hollow microporous organic nanospheres (NH2‐HMONs) were successfully synthesized by a combination of hyper‐crosslinking mediated self‐assembly process and a post‐modification strategy. Benefiting from amino groups and hollow microporous structure, the resultant NH2‐HMONs can be used to immobilize Pd nanoparticles (Pd@NH2‐HMONs) and enhance the adsorption capacity for iodine. The obtained Pd@NH2‐HMONs exhibited outstanding catalytic activity for hydrogenation of nitroarenes to aniline analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Subsequently, a pair of reversible redox reactions ( O 1 and R 1 ) occurred between p‐NP and hydroxyl aminophenol. [ 46,47 ] …”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, a pair of reversible redox reactions ( O 1 and R 1 ) occurred between p‐NP and hydroxyl aminophenol. [ 46,47 ] …”
Section: Resultsmentioning
confidence: 99%
“…Compared with the reported adsorption materials (Table S4), EDTA-HMONs-BA has better adsorption capacity, due to the introduction of EDTA functional groups and the porous properties of hollow organic nanospheres, which can bring promising pathways to enhance metal ions diffusion and increase binding sites during the ChemistrySelect adsorption process. [26] Moreover, the related coefficient of Temkin model also indicates that the adsorption process of the adsorbent is mainly from chemical interaction. [44] In DÀ R isotherm The value of adsorption energy (E) also indicates whether the adsorption process of the adsorbent belongs to chemical adsorption or physical adsorption.…”
Section: Adsorption Isotherms Studiesmentioning
confidence: 99%
“…[25] Specially, the existence of the hollow cavity in HMONs could promote mass transfer and increase the chelating sites, which can greatly improve the adsorption performance with the simultaneous application of physical adsorption and chemical adsorption. [26] It has been reported that the functionalized hollow porous materials have a good effect on the adsorption of dyes, [27] pollutants, [28] organic vapor, [29] and so on. Moreover, functionalized hollow porous materials can be used in the removal of metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…[22,24] On the other hand, grafting amino groups in the porous structures of HCPs by post-synthetic modification often requires multiple steps owing to the lack of reactive sites in the networks. [19,25] Therefore, it is still a big challenge to find an efficient procedure to prepare HCPs enriched with aminofunctionalized pores and high surface area. In 2012, Comotti et al reported the polymerization of small molecular monomers in the confined pores of MOPs that could overperform the previous modification methods.…”
Section: Introductionmentioning
confidence: 99%